(untitled) (Colloquia Comparativa Litterarum, 2025)
In the paper, an attempt has been made to comment on the adapted (Bulgarianised) works from the mid-19th century in connection with the contextualisation of the creativity of popular Bulgarian Revival writers, such as Joachim Gruev, Rashko Blaskov and Petko Slaveykov. These works, standing on the border of translations and original literature, contain religious motifs and are closer to the worldview of the Bulgarian recipient. Also, the study considers whether there is a change of religious concepts from the original work and draws attention to typical Bulgarian constructs that express the significance of the spiritual experience.